Analysis of the Healthy Family Index: The Impact of Implementing the Healthy Indonesia Program with Family Approach - Saleha, Sitti; Katiandagho, Dismo; Kushartanti, Roro; Karlina, Haura; Irmawati, Irmawati; Alam, Syamsul (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
The Healthy Indonesia Program with Family Approach (PIS-PK) is a primary initiative enforced by the current government to enhance the quality of family life and public health. In this context, the assessment of the Healthy Family Index (IKS) is essential for implementing appropriate interventions and efforts to prevent chronic diseases at the family level. Measurement indicators of IKS include healthy, pre-healthy, and unhealthy family categories. Therefore, this study aimed to analyze IKS based on PIS-PK in Jeneponto Regency, South Sulawesi in Indonesia. A quantitative design with an analytical survey was used to measure IKS across the entire family population in the Jeneponto Regency Health Center working area, totaling 1,321 households. The total sampling method was applied, and data from 12 healthy family indicators were evaluated following the IKS formula. The results showed that the average IKS value ranged from 0.59 to 0.77, representing unhealthy, pre-healthy, and healthy family, which constituted 12%, 54.35%, and 33.5% of the examined population, respectively. High numbers of family fell in the pre-healthy and unhealthy categories due to limited participation in family planning program (55.11%), non-utilization of official facilities for childbirth (11.65%), lack of exclusive breastfeeding practices over 7–23 months (10.14%), and absence of weight monitoring at Posyandu (5.59%). Consequently, integrated efforts and cross-sectoral engagement are crucial for improving IKS status.